Sampling of the anterior apical region results in increased cancer detection and upgrading in transrectal repeat saturation biopsy of the prostate. (14th May 2015) - Seles, Maximilian; Gutschi, Thomas; Mayrhofer, Katrin; Fischereder, Katja; Ehrlich, Georg; Gallé, Guenter; Gutschi, Stefan; Pachernegg, Oliver; Pummer, Karl; Augustin, Herbert
Abstract : Objective: To evaluate whether biopsy cores taken via a transrectal approach from the anterior apical region of the prostate in a repeat‐biopsy population can result in an increased overall cancer detection rate and in more accurate assessment of the Gleason score. Patients and Methods: The study was a prospective, randomised (end‐fire vs side‐fire ultrasound probe) evaluation of 288 men by repeat transrectal saturation biopsy with 28 cores taken from the transition zone, base, mid‐lobar, anterior and the anterior apical region located ventro‐laterally to the urethra of the peripheral zone. Results: The overall prostate cancer detection rate was 44.4%. Improvement of the overall detection rate by 7.8% could be achieved with additional biopsies of the anterior apical region. Two tumours featuring a Gleason score 7 could only be detected in the anterior apical region. In three cases (2.34%) Gleason score upgrading was achieved by separate analysis of each positive core of the anterior apical region. A five‐fold higher cancer detection rate in the anterior apical region compared with the transition zone could be shown. Conclusion: Sampling of the anterior apical region results in higher overall cancer detection rate in repeat transrectal saturation biopsies of the prostate. Specimens from this region can detect clinically significant cancer, improve accuracy of the Gleason Scoring and therefore may alter therapy.